(untitled) (مجلة ديالى للبحوث الانسانية, 2022)
The present study sheds light on the crucial role of social media generally and personal learning networks specifically in applying the aspects of teacher development specially in experiencing reflective practice among teachers. The study aims at ensuring full understanding of the term reflective practice by the target teachers, identifying teachers’ attitudes toward using personal learning networks in applying reflective practice and then comparing their attitudes based on gender and age variables. The study also tries to clarify the main social media applications that teachers tend to use. Sixty teachers were chosen arbitrarily from different secondary schools in Baghdad to represent the study sample. A constructed questionnaire was used by the researchers after ensuring its face validity. After dealing with the results statistically, they show that the teachers have positive attitudes towards using personal learning networks in reflective practice. They also clarify that the use of group discussion via Viber, Facebook and Whatsapp applications are the most preferable among Iraqi teachers